Analysis of the salt exclusion phenotype in rooted leaves of grapevine (Vitis spp.). (16th January 2018) - Walker, R.R.; Blackmore, D.H.; Gong, H.; Henderson, S.W.; Gilliham, M.; Walker, A.R.
Abstract: Background and Aims: Rooted leaves were used to analyse the salt exclusion phenotype in grapevines. Genotypes included rootstocks 140 Ruggeri and K51‐40 and cultivar Cabernet Sauvignon – respectively, good, poor and intermediate chloride excluders. Methods and Results: We investigated the effect of short‐term salt treatment on the chloride, sodium and potassium concentration of organs and whole rooted leaves and the time course of chloride accumulation in salt‐treated, whole rooted leaves. The effect of Control and salt plus low and high nitrate concentration on chloride and nitrate concentration in organs was assessed. Salt treatment increased chloride and sodium concentration in all organs but had no effect on potassium concentration. The chloride concentration of whole rooted leaves and the sodium concentration of lamina and petiole were similar between salt‐treated rooted leaves of 140 Ruggeri and K51‐40; 140 Ruggeri accumulated more chloride in roots and less in leaf (petiole and lamina) than K51‐40. Roots of salt‐treated 140 Ruggeri and K51‐40 responded to higher external nitrate by decreasing chloride concentration and increasing nitrate concentration. Conclusions: Restricted transport of chloride to the leaf and greater storage in roots is a feature of the chloride exclusion phenotype in rooted leaves. The short‐term capacity of 140 Ruggeri for chloride exclusion from the leaf was reduced in the salt plus high nitrate treatment. This was linked to higher nitrate and reduced chloride accumulation in roots. Significance of the Study: The chloride exclusion phenotype in rooted leaves was shown to involve greater partitioning to roots and less to the leaf, rather than differences in net chloride accumulation by whole rooted leaves.